A comparative study for in-vitro drug release profile using flow-through cell and dialysis bag. - Chew, Siao Chien. (2010)
Many new and existing drugs fail to be fully utilized due their limited bioavailability. Hence, nanoparticles have been gaining increased attention and with its potential to enhance bioavailability with higher dissolution rates. An adequate method must be developed to quantify the rate of change accompanied by a decrease in particle size with different formulations. This project aimed to perform in-vitro dissolution study to compare the flow-through cell (FTC) method and the dialysis bag method for potential nano-size dry powder drug particles evaluation. It will also investigate how various parameters (flow rate and stirring rate) helped to bring the experimental data closer to in-vivo dissolution data. The two setups were first validated with Aspirin powder to verify the effects of the proposed parameters. Promising results were obtained and the experiments were continued with Spray Freeze Dried Aspirin and Aspirin-loaded Silica nanoparticles. Their results supported that higher stirring rate for the dialysis bag and higher flow rate for the flow-through cell brought about a faster dissolution profile. Comparing the data obtained, it was also observed that effect of flow rate was more discriminating and has good potential to be used to simulate in-vivo testing.